The comparative effectiveness of first-line treatment EGFR TKIs in Asian lung cancer population: A systematic review and meta-analysis - Maria Wisnu Donowati,, Erna Kristin, Susanna Hilda Hutajulu, Dwi Endarti, Ricvan Dana Nindrea (Journal of Applied Pharmaceutical Science, 2024)
Nonsmall cell lung cancer is the most common carcinoma in Asia with more than half identified as epidermal growth factor receptor mutation-positive (EGFRm+). First- and second-generation EGFR tyrosine kinase inhibitors (TKIs), a targeted therapy type, improved overall survival compared to platinum-based chemotherapy. We conducted an updated review comparing the clinical effectiveness of EGFR TKIs as a first-line treatment in Asian populations with EGFRm+. This systematic search was conducted in six databases, resulting in 30 eligible articles, which represented Asian ethnicity and were appraised quantitatively using the GRACE checklist. Thirteen eligible studies and 3,465 patients were included in the meta-analysis. Two models of effectiveness comparison were used to measure the pooled size effect: afatinib and dacomitinib. Afatinib in patients with brain metastases had a higher risk of progression and death, but lower time to treatment failure (TTF). Never-smoking patients had lower risk of TTF and death, but equivalent risk for progression. Dacomitinib had a lower risk of progression and death. Exon 19 deletion (e19del) or exon 21 substitution (L858R) benefited more from the second generation. L858R had a higher risk of survival, progression-free, and overall survival than e19del with second-generation agents. Coexisting e19del or L858R in uncommon mutation is associated with longer progression than without it.
Keywords: Lung cancer, Asian, epidermal growth factor receptor mutation, tyrosine kinase inhibitors